Bioinspired silica-infiltrated zirconia bilayers: Strength and interfacial bonding - Toyama, Dominique Yukie [UNESP]; Alves, Larissa Marcia Martins [UNESP]; Ramos, Gabriela Freitas [UNESP]; Campos, Tiago Moreira Bastos; de Vasconcelos, Getúlio; Borges, Alexandre Luiz Souto [UNESP]; de Melo, Renata Marques [UNESP] (Elsevier, 2019)
Conventionally veneered zirconia restorations are susceptible to chipping and spalling of the veneering material. The novel translucent zirconias were developed to overcome such issues, although layered zirconia restorations can be re-designed to improve mechanical performance. Thus, the aim of this study was to analyze the strength and structural reliability of zirconia bilayers using conventional (porcelain ceramic under tensile stress) and bioinspired (zirconia under tensile stress) configurations. Sol-gel silica infiltration served as a smooth transition between the zirconia and veneering porcelain. Failure mode and interfacial adhesive mechanism were analyzed using scratch test and interfacial indentation. Bilayered specimens were produced for biaxial flexural testing with Y-TZP and pressed ceramic, which were further divided into four groups (n = 30): Conventional (C), Infiltrated conventional (IC), Bioinspired (B) and Infiltrated bioinspired (IB). The results of biaxial flexural strength tests were analyzed by Weibull analysis (95% CI) for determination of the Weibull modulus (m). The infiltration layer was characterized by XRD and SEM, FEG-SEM and EDS. The bioinspired infiltrated group was the most reliable (m = 9.59), although the fine damage of veneered conventional (conventional) zirconia demonstrated its superior resistance to scratching and debonding. Therefore, the filling of superficial defects by zirconia silicate demonstrated the need for mechanical retention for better porcelain adhesion.
Keywords: Ceramics; Dental porcelain; Silica gel